THE EFFECT OF BITTER MELON JUICE ON BLOOD PRESSURE IN HYPERTENSIVE PATIENTS IN JAGAMUKTI VILLAGE, SURADE HEALTH CENTER WORKING AREA - Utami, Anniswah; Alamsyah , Azhar Zulkarnain; Mulyadi, Egi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
This study aims to analyze the effect of consuming bitter melon juice on blood pressure in hypertensive patients in Jagamukti Village, Surade Health Center's working area. Hypertension is a non-communicable disease with a high prevalence that requires serious attention. This study used a quasi-experimental design with a one-group pretest-posttest design, involving 15 respondents selected using cluster sampling. Data were analyzed using parametric statistical tests with a T-test. The results showed that the average systolic blood pressure before the intervention was 151 mmHg, while after the intervention, it decreased to 145 mmHg. Statistically, there was a significant difference with a p-value of 0.000 (<0.05), indicating that bitter melon juice is effective in lowering blood pressure in hypertensive patients. Most respondents were female (60%) aged 46–55 years (66.7%), and the majority worked as housewives (60%). Bitter melon, rich in potassium and possessing diuretic effects, effectively lowers sodium levels in the blood, helping to reduce blood pressure. This study reinforces the potential of bitter melon as a safe and natural non-pharmacological intervention for hypertension. These findings are expected to encourage the use of herbal plants in the management of hypertension.